Increased prevalence of neural monitoring during thyroidectomy: Global surgical survey. (30th July 2019) - Feng, Allen L.; Puram, Sidharth V.; Singer, Michael C.; Modi, Rahul; Kamani, Dipti; Randolph, Gregory W.
Abstract : Objective: To investigate intraoperative nerve monitoring (IONM) use among thyroid surgeons. Methods: A 25‐question survey was used to assess attitudes regarding IONM use. Surveys were sent to surgeons registered to the American Academy of Otolaryngology–Head and Neck Surgery, International Association of Endocrine Surgeons, and American Head and Neck Society. Results: Among 1, 015 respondents, 83% reported using IONM (65.1% always using IONM and 18.1% reporting selective use). For selective users, a majority reported using IONM for reoperative cases (95.1%) and in cases with preoperative vocal cord paralysis (59.8%). When comparing location, there was a significant difference in IONM implementation ( P < 0.001), with 70.4% of North American responders using it ubiquitously compared to 27.4% of non‐North American responders. Preoperative laryngeal exam was performed more universally by North American surgeons and more selectively by non‐North American surgeons ( P < 0.001). Other attitudes toward their implementation and the postoperative laryngeal exam were similar. Surgeons ≤45 years of age and those with ≤15 years of practice used IONM more than their peers ( P < 0.001). Thyroid surgery volume, fellowship training, and type of practice had no bearing on IONM use. Conclusion: The prevalence of IONM in thyroid and parathyroid surgeries has increased significantly over the past decade, with 83% of surgeons using IONM in some or all cases. Although IONM use may be more ubiquitous in North America, attitudes toward its implementation and pre‐ and postoperative laryngeal exams are fairly uniform. IONM use is more prevalent among younger surgeons, whereas its use has no correlation with thyroid surgery volume or type of practice. Level of Evidence: 4 Laryngoscope, 130:1097–1104, 2020